Cadreization of Women Ulama in Rahima: Epistemological Analysis of Husein Muhammad's Tafsir - Suhayati, Mimi; Febriani, Nur Arfiyah; Mosher, Lucinda; Zarli, Fadli (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This study examines Husein Muhammad's epistemology of interpretation in the context of women's empowerment, specifically through the Women's Ulama Training Program (PUP) by the NGO Rahima. Husein Muhammad's epistemology interpretation includes explanations about women's position in the Qur'an, the importance of knowledge for women, and women's leadership. His sources of interpretation encompass the Qur'an, Hadith, and the opinions of scholars, with validity tested using coherence and correspondence theories. Rahima has developed an epistemological model that uses a rational and critical approach to interpreting the Qur'an, focusing on inclusivity and justice. This research employs qualitative and descriptive-analytical methods with the maudhu’i method. Primary data sources include the book "Epistemology of Contemporary Interpretation" by Abdul Mustaqim, "Women Ulama in the Historical Spotlight" by Husein Muhammad, educational modules by Hilmi Ali Yafie, and Rahima's website. The study results indicate that PUP is an academic program that promotes a deep understanding of religion, gender equality, and knowledge of women's rights. The program aims to form competent female ulama who can contribute positively to society.